PERINATAL AND MATERNAL OUTCOME OF PREECLAMPSIA WITH SEVERITY FEATURE MANAGED EXPECTANTLY AT ST. PAUL’S HOSPITAL MILLENNIUM MEDICAL COLLEGE (SPHMMC), 2021, ADDIS ABABA, ETHIOPIA. A CROSS SECTIONAL STUDY - Kebede, Birhanu; Solomon, Ananaya; Abraham, Tizita (Ethiopian Journal of Reproductive Health, 2024)
ABSTRACT Background Preeclampsia refers to the new onset of hypertension and proteinuria after 20 weeks of gestation in a previously normotensive woman. It is labeled as Preeclampsia with severe features when one of the severity signs occurs. Worldwide, Preeclampsia occurs in up to 7.5 percent of pregnancies and 10 - 15 % of direct maternal deaths are associated with preeclampsia and eclampsia. Majority of adverse maternal and perinatal outcome occur in Preeclampsia with severe features and when Preeclampsia occurs remote from term ( ). Objective The main objective of this study was to determine the maternal and perinatal outcome of Preeclampsia with severe features managed expectantly at SPHMMC in one year period. Materials and Methods: Facility based cross-sectional study was conducted. The study participants were selected consecutively by including all mothers admitted during the study period (January 2021 to December 2021 G.C.) with the diagnosis of Preeclampsia with severe features to SPHMMC that fulfill the inclusion criteria. Data taken was, the patients chart and a direct patient interview using pre-tested & structured questionnaire. Collected data was entered in to Epi info version 7 & analysis was made through SPSS version 25. Descriptive statistics, tables & figures was used to describe the study finding. Result –the mean days of prolongation of pregnancy was 11.5 days with slight increment of maternal complication from expected proportion that completely resolved postpartum. The most common maternal complications were HELLP syndrome (15.1%) and abruptio placenta (7.2%). There were 21 perinatal deaths (08 still births and 13 neonatal deaths) that give perinatal mortality rates of 276 per 1000 live births. The rate of NICU admission was 66.7% and the neonatal survival to seventh day was 71.7%. Only 66(90.4%) of the women were a good candidate for expectant management. Magnesium sulphate and steroid (dexamethasone) at admission was given 100% but 8.2% of the mothers didn’t get magnesium sulphate during intra partum and post partum period. Conclusion / Recommendation - Proper selection of pregnant mothers with pre-eclampsia with severity feature and Close and frequent maternal and fetal surveillance during expectant management is associated with a good perinatal outcome without significant difference in maternal complication. Key Words: pre-eclampsia ,Perinatal outcome, maternal complication.